Effectiveness of Cognitive Interventions Based on New Technologies on Cognitive Function of Children with Attention-Deficit/Hyperactivity Disorder in Iran: A Meta-Analysis Study - Faezeh Shabanali Fami; Sogand Ghasemzadeh; Somayeh Nejati (پژوهان, 2023)
Background and Objectives: This research aims to combine studies conducted in the field of cognitive interventions based on modern technologies (computer and neurofeedback) to improve cognitive functions among children with attention deficit/hyperactivity disorder in Iran. Materials and Methods: The method used in this study was a meta-analysis. The statistical population of this research included studies conducted in Iran. They were indexed in Persian-language databases until 2022 in the field of modern cognitive interventions concerning attention deficit/hyperactivity disorder. For this purpose, 69 studies that met the desired criteria were selected, and a meta-analysis was performed based on them. The CMA software was used to analyze the collected data. Results: The research findings showed that the effect size of these technologies in the field of computer-based interventions was equal to 0.936, that of the neurofeedback interventions was equal to 1.057, and that of the total was equal to 0.997, which, according to Cohen's table, means that these effects have a high effect. Conclusion: The results showed that cognitive interventions based on modern technologies had a positive and significant impact on improving the cognitive performance of children with this disorder.